Magnetism in dilute magnetic oxide thin films based on SnO2 - STAMENOV, PLAMEN; COEY, JOHN; VENKATESAN, MUNUSWAMY (My University, 2006)
Thin films of SnO2 prepared by pulsed-laser deposition on R-cut sapphire substrates exhibit ferromagnetic properties at room temperature when they are doped with Cr, Mn, Fe, Co, or Ni, but not with other 3d cations. Extrapolated Curie temperatures are generally in excess of 500 K. The moment of the films is roughly independent of doping level, from 0.1?15 at. %, with a value per unit substrate area of 200?100 ?B nm?2. When magnetization is expressed as a moment per 3d dopant ion, it varies from more than the spin-only value at low concentrations to less than 0.2 ?B/ion near the percolation threshold. Greatest values are found for iron. The magnetization of the films is highly anisotropic with values when the field is applied perpendicular to the substrate more than double the in-plane values. There is little hysteresis except at high doping levels. The oxides are degenerate n-type semiconductors with a Hall mobility of 100 cm2 V?1 s?1 and 1.4?1019 carriers cm?3 in a one-band model, but no anomalous Hall effect or magnetoresistance was observed at room temperature. The data are discussed in relation to (a) the donor impurity-band model of ferromagnetism in semiconductors and (b) the magnetic defect model.
PUBLISHED
Keywords: Physics